Conceptualization of aggressive driving behaviors through a Perception of aggressive driving scale (PAD). (January 2019) - Alonso, Francisco; Esteban, Cristina; Montoro, Luis; Serge, Andrea
Highlights: Aggressive driving is a major concern for Spanish drivers. Socio-demographic features explain aggressive driving perception differences. Drivers ≥30 years old, women and low-middle classes perceived more aggressiveness. Both infractions and unpunishable risky behaviors are perceived as aggressive. Drivers who had ≥3 accidents de-emphasized aggressive gestures and shouting. Abstract: Research on traffic safety has highlighted the importance of studying and intervening in aggressive driving in order to reduce crashes and accidents. The main objective of this work is to describe the perception of what people consider an aggressive behavior, and their perception of which are the most aggressive acts performed when driving. The sample was composed of 1079 Spanish drivers aged over 14. They participated in a national telephone survey, completing a questionnaire which gathered socio-demographic data and information on the drivers' profiles, containing a "Perception of aggressive driving Scale (PAD)". The unifactorial ANOVA test for repeated measures of the General Linear Model (GLM) with α = 0.05 procedure was used for the comparison of mean values. Results show that drivers tend to make higher valuations regarding the aggressive character of the PAD ( M  = 7.86 SD =  0.05). The situation that most concerned Spanish drivers was "To produce damage to other people with some type of object or weapon" ( M  = 9.47 SD =  0.05), which does not necessarily correspond to the driving context. Differences in perception were found depending on socio-demographic variables. Women, drivers over 29 years old, low-middle social classes, and drivers who had suffered two accidents, tended to evaluate PAD as more aggressive. These findings suggest that differences in the perception of aggressive behaviors depend on social situations and on the driver's personal features. Finally, the findings of this research will help road safety researchers understand the concept of aggressiveness under different perspectives, and take into account the existing differences between dangerous and punishable behaviors. Moreover, these outcomes showed the necessity to deepen the research on those behaviors that Spaniards perceive as aggressive, and to develop knowledge on why the perception of aggressiveness changes according to the characteristics of the population, and how this perception is reflected in people's attitudes and behaviors towards road safety.